Curriculum redesign and transition from traditional education to a dual education - Zavala Sañudo, Carmen Guadalupe (Universidad de Sonora, 2020)
The objective of this article is to show the importance that represent the techniques of education-dual in the curricular models in the Superior Education Institutions, as well as, to point out the benefit of the inclusion of education dual model as the proposed in the present research. The application of this modality in the educative sector represents a cooperation strategy and coordination between the students, institutions and the companies, with the purpose to provide the student of knowledge, abilities and skills to permit them to face of the labor field. These knowledges will allow the students to count with "labor competence" to potentiate in the labor activities.